COMMUNITY SATISFACTION INDEX FOR SERVICES AT THE HULU SUNGAI UTARA DISTRICT REGIONAL LIBRARY - Junaidi Junaidi; Rina Emilyana; Siti Rabiah (PT. Antis International Publisher, 2025)
Objective: This study aims to evaluate the level of community satisfaction with the services provided by the Hulu Sungai Utara District Regional Library and determine the Community Satisfaction Index (IKM) based on several service indicators. Method: A descriptive quantitative research design was employed, utilizing a sample of 94 respondents. Data were collected through questionnaires, observations, literature reviews, and documentation. The research used the Public Satisfaction Index (IKM) analysis, as prescribed by PERMENPAN-RB No. 14 of 2017, which applies a Likert scale to assess satisfaction across nine service elements. Results: The study found a Community Satisfaction Index of 76.1, placing the service quality in the